The effect of brand image and price on purchase decisions for erigo products with product quality as a mediation variable - Fauzi Janothama; Edy Purwo Saputro (Institute of Computer Science (IOCS), 2026)
Research on purchasing decisions in the fashion industry continues to show inconsistent findings regarding the roles of brand image, price, and product quality. In the Indonesian context, Erigo represents a rapidly growing local brand with strong visibility, yet limited empirical evidence explains the factors driving consumers’ purchase decisions toward it. This study examines how Brand Image and Price influence Purchase Decisions by integrating Product Quality as a mediating variable. A quantitative method was employed, and data were collected through a structured questionnaire distributed to consumers with prior experience using Erigo products. All measurement indicators were adapted from established literature and assessed using validity and reliability testing. SmartPLS was used for analysis, including measurement and structural model evaluation with a 5% significance level. The findings indicate that Brand Image does not directly influence Purchase Decisions but significantly improves Product Quality, which strongly drives purchasing behavior. Price shows both direct and indirect effects through Product Quality, making it a key determinant of purchase decisions. Overall, the study highlights the importance of maintaining strong product performance and strategic pricing alignment to enhance consumer purchasing behavior toward Erigo products.